internally displacement persons; students; fears; PTSD; stress events - Луценко, Олена Львівна; Цапкова, Анастасія Сергіївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The aim was to identify which psychological state experience students – internally displaced persons (IDPs), particularly how they feel fears and stress in comparison with the control group (ordinary students). In the study there were involved 63 students of classical university of 1-4 years of studying of different faculties. Experimental group included 35 students which were displaced from Anti-Terrorist Operation Zone (10 males and 25 females) and control group included 28 ordinary students (13 males and 15 females). The mental state of students-IDPs can be characterized by worse features than state of ordinary students, which manifested in a greater tendency to experience fears and less resistance to stress because of experienced traumatic events. The students-IDPs’ severity of PTSD symptoms are connected with their level of fears, unlike the PTSD symptoms severity of the ordinary students which are associated with their experience of actual stressful events. PTSD symptoms of the students-IDPs have not reached clinically meaningful level that can be explained by quite afﬂ uent conditions in the new region where they resettled, and the perspectives of studying at the prestigious university, in which they were enrolled.